The 1960s on film - Willis, Jim, 1946 March 19-; Miller, Mark, 1992- (Hollywood history., 2021)
"The 1960s on Film tells the narrative of the 1960s through the lens of the movie camera, analyzing ten films that focus on the people, events, and issues of the decade"--